2017
DOI: 10.2131/jts.42.137
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing detects variants of genes that mediate response to anticancer drugs

Abstract: -Certain interindividual differences affecting the efficacy of drug treatment and adverse drug reactions are caused by genetic variants, and their phenotypic effects differ among ethnic groups. In this study, we used whole exome sequencing (WES) systematically to identify germline mutations that influence the activities of drug-metabolizing enzymes, as well as that of a transporter. We analyzed DNA isolated from blood samples from 2,042 Japanese patients with diverse cancers. We identified sequence variants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In this study, we systematically detected selected SNPs using whole-exome sequencing, theses variants were visually confirmed by Integrative Genomics Viewer. [17] Variants at the following 8 sites were investigated: the opioid m receptor 1 variant rs1799971, [18] the opioid d receptor 1 variant rs2234918, [19] the opioid k receptor 1 variant rs1051660, [20] the catechol-Omethyltransferase (COMT) variant rs4680, [21] the dopamine receptor D2 variant rs6275, [22] the P-glycoprotein adenosine triphosphate binding cassette B1 variant rs1045642, [23] the Gprotein regulated inward rectifier potassium channel 2 variant rs2070995, [24] and the fatty acid amide hydrolase variant rs324420. [25] Incidence of each adverse effect was compared between variants.…”
Section: Genetic Variantsmentioning
confidence: 99%
“…In this study, we systematically detected selected SNPs using whole-exome sequencing, theses variants were visually confirmed by Integrative Genomics Viewer. [17] Variants at the following 8 sites were investigated: the opioid m receptor 1 variant rs1799971, [18] the opioid d receptor 1 variant rs2234918, [19] the opioid k receptor 1 variant rs1051660, [20] the catechol-Omethyltransferase (COMT) variant rs4680, [21] the dopamine receptor D2 variant rs6275, [22] the P-glycoprotein adenosine triphosphate binding cassette B1 variant rs1045642, [23] the Gprotein regulated inward rectifier potassium channel 2 variant rs2070995, [24] and the fatty acid amide hydrolase variant rs324420. [25] Incidence of each adverse effect was compared between variants.…”
Section: Genetic Variantsmentioning
confidence: 99%
“…We analyzed the genes encoding CYP isoforms ( CYP1A2 , CYP2A6 , CYP2B6 , CYP2C9 , CYP2C19 , CYP2D6, CYP2E1 , CYP3A4 , and CYP3A5 ), thiopurine methyltransferase ( TPMT ), dihydropyrimidine dehydrogenase ( DPYD ), N-acetyltransferase 2 ( NAT2 ), UDP glucuronosyltransferase family member A1 ( UGT1A1 ), catechol-O-methyltransferase ( COMT ), ATP binding cassette subfamily G member 2 ( ABCG2 ), cytidine deaminase ( CDA ), alcohol dehydrogenase 1B ( ADH1B ), aldehyde dehydrogenase 2 ( ALDH2 ), 5-methyltetrahydrofolate-homocysteine methyltransferase reductase ( MTRR ), and methylenetetrahydrofolate reductase ( MTHFR ) in this study because the variants of these genes have been reported to affect drug response in Japanese populations 11 , 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Widespread use of next-generation sequencing has enabled comprehensive investigation of genetic variants, such as drug-metabolizing enzymes, using whole-genome sequencing (WGS) and whole-exome sequencing (WES). However, genes with high homologies, such as CYP genes, still have unanalyzable genetic variants 11 , 12 . Therefore, we constructed a unique genetic variant panel that mainly covers the exon regions of 20 genes, including both lifestyle- and cancer-related genes, focusing on drug-metabolizing enzyme-coding genes that influence the therapeutic and adverse effects of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the genes encoding CYP isoforms ( CYP1A2, CYP2A6, CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP2E1, CYP3A4, and CYP3A5), thiopurine methyltransferase (TPMT), dihydropyrimidine dehydrogenase (DPYD), N-acetyltransferase 2 (NAT2), UDP glucuronosyltransferase family member A1 (UGT1A1), catechol-O-methyltransferase (COMT), ATP binding cassette subfamily G member 2 (ABCG2), cytidine deaminase (CDA), alcohol dehydrogenase 1B (ADH1B), aldehyde dehydrogenase 2 (ALDH2), 5methyltetrahydrofolate-homocysteine methyltransferase reductase (MTRR), and methylenetetrahydrofolate reductase (MTHFR) in this study because the variants of these genes have been reported to affect drug response in Japanese populations 11,22 .…”
Section: Construction Of An In-house Custom Dme Panelmentioning
confidence: 99%
“…Widespread use of next-generation sequencing has enabled to comprehensively investigate genetic variants, such as drug-metabolizing enzymes, using whole-genome sequencing (WGS) and whole-exome sequencing (WES). However, genes with high homologies, such as CYP genes, still have unanalyzable genetic variants 11,12 . Therefore, we constructed a unique genetic variant panel that mainly covers the exon regions of 20 genes, including both lifestyle-and cancer-related genes, focusing on drugmetabolizing enzyme-coding genes that in uence the therapeutic and adverse effects of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%